Creative historiography - Maliwat, Nathaniel M. (College of Arts and Letters, University of the Philippines Diliman, 2011)
Creative Nonfiction has the unique ability of appropriating other genres for its own use. The writing of history has not escaped the techniques commonly used in Creative Nonfiction - scenes, dialogue, characterization and approach - and known historians Nick Joaquin and Ambeth Ocampo had explored these techniques in rendering the past. The blurring of line between genres becomes problematic in light of criticism. Thus, two questions are posed in this essay: (1) how should history be praised as Creative Nonfiction? (2) Is a historical work presented with style serious? To answer these questions, the author establishes the fact that history essays by Joaquin and Ocampo satisfy the two basic elements of Creative Nonfiction: facts researched and facts presented with style. Furthermore, the author argues for validity of style, or individuality, in historiography. A comparative study of Joaquin and Ocampo's essay is then explored to illustrate how individuality enters the writing of history.